Evaluación Financiera a la Compañía “DISTAL S.A.” de la Ciudad de Loja. Período: 2014-2015 - Narváez Granda, Andrea Gianella (2017)
The thesis entitled "FINANCIAL EVALUATION COMPANY" Distal S.A. "CITY OF LOJA. PERIOD: 2014 - 2015 ", held as a precursor to choose the Degree of Engineer in Accounting and Auditing CPA, the National University of Loja requirement. The same that has been developed given its relevance in the increasingly competitive business environment, aims to analyze, organize and evaluate the results of the analysis and forecasts made, helping the company to minimize risks and seize the opportunities for thus increasing profitability. For the general objective, we proceeded to make a financial assessment it allowed to know the management of the financial resources to contribute to decision-making and propose alternatives that improve the performance of the company As the first phase of the financial evaluation, we have the diagnosis or financial analysis, which was made based on the financial statements through the vertical, horizontal analysis and application of financial reasons liquidity, debt, profitability and activity became known the company; economic and financial performance was analyzed through dupont system, which allowed them to propose alternatives for 6 improvement that lead to increased levels of profitability, and thus achieve the permanence of the company. As a second phase of financial evaluation, is itself the evaluation of the company, for which a financial projection was made, based on the information issued by the company, which forecast sales and purchases was developed, tickets , cash outflows to determine the cash budget and to establish the deficit or surplus cash in the periods projected, then pro forma financial statements were prepared for the years 2016-2020, applying the method of percentage increase, which shows whether the company needs financing or not, whether it is internal or external, so you can take corrective action promptly. As the last one met the specific objective, a financial evaluation report was presented that allowed to know the economic-financial situation concluding that the company has serious collection problems, ie it is not recovered within the established time of 30 days, Because it is recovered in a 61-day period, ie it has a surplus of 31 days, causing the company to lack liquidity, so it is suggested to implement adequate collection policies, making a more adequate registration of its customers.